Bond rearrangement during Coulomb explosion of water molecules - Leonard, M.; Sayler, A. M.; Carnes, K. D.; Kaufman, Emily M.; Wells, E.; Cabrera-Trujillo, R.; Esry, B. D.; Ben-Itzhak, I. (My University, 2019)
Bond rearrangement, namely the dissociation of water ions into H2++O(q−1)+ (q=1–4) following fast ion-impact ionization, unexpectedly occurs following multiple ionization of water in spite of the presumably fast “Coulomb explosion” of the transient molecular ion. Furthermore, the branching ratio of bond rearrangement is found to be nearly equal for each level of ionization, q. In addition, formation of H2+ is more than twice as likely to occur from the lighter water isotopologue H2O+ than D2+ from D2O+. These findings are consistent with the ground state dissociation mechanism in which a fast projection of the ground state nuclear wave function onto the vibrational continuum of the cation potential energy surface is sometimes followed by H2+ formation.